2023
DOI: 10.25248/reas.e12452.2023
|View full text |Cite
|
Sign up to set email alerts
|

Investigação dos fatores de risco pré-estabelecidos para perdas auditivas em idosos

Abstract: Objetivo: Investigar os fatores de risco pré-estabelecidos para perdas auditivas em idosos tendo em vista a conversão dos vários fatores de risco relatados na literatura. Métodos: Refere-se a uma pesquisa de coorte, transversal, desenvolvida em um Hospital do Acre. O projeto foi aprovado pelo Comitê de Ética da Universidade Veiga de Almeida CEP/UVA nº (12546113.8.0000.5291). A amostra foi composta por 100 idosos, frequentadores do grupo de terceira idade na cidade de Rio Branco Acre. Resultados: Dentre os muit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Visual deficit is common in the population of individuals with T2DM, increasing the likelihood of falls by up to 4 times. Worsening vision causes a series of problems such as self-administration of medications, in addition to difficulty adhering to treatment, which can lead to blindness or diabetic retinopathy 25 . These problems result in worsening balance, indicating a deficiency in the visual system, the system responsible for PC 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual deficit is common in the population of individuals with T2DM, increasing the likelihood of falls by up to 4 times. Worsening vision causes a series of problems such as self-administration of medications, in addition to difficulty adhering to treatment, which can lead to blindness or diabetic retinopathy 25 . These problems result in worsening balance, indicating a deficiency in the visual system, the system responsible for PC 1 .…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the increase in age in the older adults increases the occurrence of hearing loss, when added to T2DM, these individuals tend to the increased the likelihood of falls. Studies report that hearing loss is related to cognitive loss 25 . Common problems found in individuals with decompensated diabetes 26 .…”
Section: Discussionmentioning
confidence: 99%
“…O deficit visual é comum na população de indivíduos com DM2, aumentando a probabilidade de quedas em até 4 vezes. A piora na visão acarreta uma série de problemas, como a autoadministração de medicamentos, além de dificuldades na adesão ao tratamento, o que pode levar à cegueira ou retinopatia diabética 25 . Esses problemas resultam em um agravamento do equilíbrio, indicando deficiência no sistema visual, responsável pelo CP 1 .…”
Section: Discussionunclassified
“…Observou-se que o aumento da idade em idosos está associado ao aumento da ocorrência de perda auditiva; somado ao DM2, esses indivíduos tendem a ter uma maior probabilidade de quedas. Estudos relatam que a perda auditiva está relacionada à perda cognitiva 25 . Problemas comuns esses, encontrados em indivíduos com diabetes descompensado 26 .…”
Section: Discussionunclassified